Evaluation of Thiol Disulfide Homeostasis and Ischemia-Modified Albumin Levels as an Indicator of Oxidative Stress in Acne Vulgaris - Balık, Zeynep Büşra; Balık, Ahmet Rıfat; Fırat Oğuz, Esra; Erel, Özcan; Tunca, Mustafa (Dermatology Practical & Conceptual, 2023)
Introduction: Acne vulgaris (AV) is the most common skin disease. AV is a skin disease often associated with oxidative stress. Thiols and ischemia modified albumin (IMA) analysis are used as oxidative stress markers.Objectives: In this study, it was aimed to evaluate the blood levels of thiols and IMA, which are accepted as oxidative stress markers, and to determine the severity of the disease in AV patients whose severity is determined by the global acne score rate (GAS).Methods: Thiol parameters and IMA values ​​were measured spectrophotometrically in blood samples taken from patients and controls. Determine VAS values ​​in AV patients. The thiol and IMA values ​​obtained were compared between the patient and control groups and their correlation with the patient's VAS values ​​was evaluated.Results: In our study, in acne patients, native thiol (NT), total thiol (TT) and index 3 (I3=NT/TT*100) were significantly lower than the control group, disulfide (SS), index 1 (I1=SS/NT*100), index 2 (I2=SS/TT*100) and IMA values were found to be significantly higher. GAS values, which are accepted as an indicator of the degree and severity of acne disease, and SS, I1 and I2 showed a positive correlation, while I3 showed a negative correlation.Conclusion: Our study suggests that oxidative stress associated with AV disease pathogenesis may occur through mechanisms dependent on thiol and IMA levels. Therefore, in AV, oral supplementation or topical application of antioxidants may be a good way to increase drug efficacy or prevent potential harm.